Cyclooxygenase-2 Inhibition Reduces Autophagy of Macrophages Enhancing Extraintestinal Pathogenic Escherichia coli Infection - Ren, Haiyan; Chen, Xuhua; Jiang, Fengwei; Li, Ganwu (Frontiers in Microbiology, 2020)
Extraintestinal pathogenic Escherichia coli (ExPEC) is one of the top pathogens responsible for bloodstream infection and severe, often fatal, sepsis. Although the virulence factors and host immune responses to ExPEC infection have been investigated, the responses to a particular ExPEC strain could be very different. In this study, we investigated the mechanisms of Cyclooxygenase-2 (COX-2) up-regulation in influencing the host defenses against infection of ExPEC XM O2:K1:H7. Our results demonstrated that ExPEC XM O2:K1:H7 infection in mouse and RAW264.7 macrophages leads to COX-2 up-regulation, and COX-2 inhibition significantly enhances ExPEC infection. The up-regulation of COX-2 in macrophages was mediated by Toll-like receptor 4 (TLR4) through the activation of p38 and extracellular signal-regulated kinase/Mitogen-activated protein kinase (ERK/MAPK) pathways. Further studies showed that COX-2 inhibition significantly decreased autophagy in macrophages during ExPEC XM O2:K1:H7 infection. Autophagy inhibition significantly enhanced, while induction reduced ExPEC XM O2:K1:H7 survival in macrophages. In addition, COX-2 inhibition significantly increased macrophage cell death during ExPEC XM O2:K1:H7 infection and increased the expression of anti-inflammatory cytokine interleukin-10 (IL-10). Our results indicate that COX-2 up-regulation benefits host defense against ExPEC XM O2:K1:H7 infection by increasing autophagy in macrophages and by reducing IL-10 expression and macrophage cell death during ExPEC infection.